Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Sure, let's solve this problem step-by-step.
### Part A: Translation Description
The translation rule given is [tex]\((x, y) \rightarrow (x + 4, y - 3)\)[/tex]. This means that we need to translate each point 4 units to the right and 3 units downwards. Hence, the translation can be described in words as:
Translate 4 units to the right and 3 units downwards.
### Part B: Vertices of [tex]\(\triangle A^{\prime} B^{\prime} C^{\prime}\)[/tex]
To find the vertices of the translated triangle [tex]\(\triangle A^{\prime} B^{\prime} C^{\prime}\)[/tex], we apply the translation rule to each of the original vertices [tex]\(A(-3, 1)\)[/tex], [tex]\(B(-3, 4)\)[/tex], and [tex]\(C(-7, 1)\)[/tex].
1. For vertex [tex]\(A(-3, 1)\)[/tex]:
[tex]\[ A' = (x + 4, y - 3) = (-3 + 4, 1 - 3) = (1, -2) \][/tex]
2. For vertex [tex]\(B(-3, 4)\)[/tex]:
[tex]\[ B' = (x + 4, y - 3) = (-3 + 4, 4 - 3) = (1, 1) \][/tex]
3. For vertex [tex]\(C(-7, 1)\)[/tex]:
[tex]\[ C' = (x + 4, y - 3) = (-7 + 4, 1 - 3) = (-3, -2) \][/tex]
Therefore, the vertices are:
[tex]\[ A' = (1, -2), \quad B' = (1, 1), \quad C' = (-3, -2) \][/tex]
### Part C: Rotation of [tex]\(\triangle A^{\prime} B^{\prime} C^{\prime}\)[/tex]
Now, we rotate [tex]\(\triangle A^{\prime} B^{\prime} C^{\prime}\)[/tex] [tex]\(90^\circ\)[/tex] counterclockwise about the origin. The rotation rule for [tex]\(90^\circ\)[/tex] counterclockwise is [tex]\((x, y) \rightarrow (-y, x)\)[/tex]. We apply this to each of the vertices [tex]\(A'(1, -2)\)[/tex], [tex]\(B'(1, 1)\)[/tex], and [tex]\(C'(-3, -2)\)[/tex].
1. For vertex [tex]\(A'(1, -2)\)[/tex]:
[tex]\[ A'' = (-(-2), 1) = (2, 1) \][/tex]
2. For vertex [tex]\(B'(1, 1)\)[/tex]:
[tex]\[ B'' = (-(1), 1) = (-1, 1) \][/tex]
3. For vertex [tex]\(C'(-3, -2)\)[/tex]:
[tex]\[ C'' = (-(-2), -3) = (2, -3) \][/tex]
The vertices of the rotated [tex]\(\triangle A'' B'' C''\)[/tex] are:
[tex]\[ A'' = (2, 1), \quad B'' = (-1, 1), \quad C'' = (2, -3) \][/tex]
### Congruency Check
To determine if [tex]\(\triangle A B C\)[/tex] is congruent to [tex]\(\triangle A'' B'' C''\)[/tex], we compare the side lengths of both triangles.
1. Original triangle [tex]\(\triangle A B C\)[/tex]:
[tex]\[ \text{Side } AB = \|A - B\| = \sqrt{(-3 - (-3))^2 + (1 - 4)^2} = \sqrt{0^2 + (-3)^2} = 3 \][/tex]
[tex]\[ \text{Side } BC = \|B - C\| = \sqrt{(-3 - (-7))^2 + (4 - 1)^2} = \sqrt{4^2 + 3^2} = \sqrt{16 + 9} = 5 \][/tex]
[tex]\[ \text{Side } CA = \|C - A\| = \sqrt{(-7 - (-3))^2 + (1 - 1)^2} = \sqrt{(-4)^2 + 0^2} = 4 \][/tex]
2. Rotated triangle [tex]\(\triangle A'' B'' C''\)[/tex]:
[tex]\[ \text{Side } A''B'' = \|A'' - B''\| = \sqrt{(2 - (-1))^2 + (1 - 1)^2} = \sqrt{3^2 + 0^2} = 3 \][/tex]
[tex]\[ \text{Side } B''C'' = \|B'' - C''\| = \sqrt{(-1 - 2)^2 + (1 - (-3))^2} = \sqrt{(-3)^2 + 4^2} = \sqrt{9 + 16} = 5 \][/tex]
[tex]\[ \text{Side } C''A'' = \|C - A\| = \sqrt{(2 - 2)^2 + (-3 - 1)^2} = \sqrt{0^2 + (-4)^2} = 4 \][/tex]
Since the side lengths of [tex]\(\triangle A B C\)[/tex] and [tex]\(\triangle A'' B'' C''\)[/tex] match, the triangles are congruent.
### Conclusion:
Yes, [tex]\(\triangle ABC\)[/tex] is congruent to [tex]\(\triangle A'' B'' C''\)[/tex].
Thus, we have provided complete and detailed steps to answer each part of the problem correctly.
### Part A: Translation Description
The translation rule given is [tex]\((x, y) \rightarrow (x + 4, y - 3)\)[/tex]. This means that we need to translate each point 4 units to the right and 3 units downwards. Hence, the translation can be described in words as:
Translate 4 units to the right and 3 units downwards.
### Part B: Vertices of [tex]\(\triangle A^{\prime} B^{\prime} C^{\prime}\)[/tex]
To find the vertices of the translated triangle [tex]\(\triangle A^{\prime} B^{\prime} C^{\prime}\)[/tex], we apply the translation rule to each of the original vertices [tex]\(A(-3, 1)\)[/tex], [tex]\(B(-3, 4)\)[/tex], and [tex]\(C(-7, 1)\)[/tex].
1. For vertex [tex]\(A(-3, 1)\)[/tex]:
[tex]\[ A' = (x + 4, y - 3) = (-3 + 4, 1 - 3) = (1, -2) \][/tex]
2. For vertex [tex]\(B(-3, 4)\)[/tex]:
[tex]\[ B' = (x + 4, y - 3) = (-3 + 4, 4 - 3) = (1, 1) \][/tex]
3. For vertex [tex]\(C(-7, 1)\)[/tex]:
[tex]\[ C' = (x + 4, y - 3) = (-7 + 4, 1 - 3) = (-3, -2) \][/tex]
Therefore, the vertices are:
[tex]\[ A' = (1, -2), \quad B' = (1, 1), \quad C' = (-3, -2) \][/tex]
### Part C: Rotation of [tex]\(\triangle A^{\prime} B^{\prime} C^{\prime}\)[/tex]
Now, we rotate [tex]\(\triangle A^{\prime} B^{\prime} C^{\prime}\)[/tex] [tex]\(90^\circ\)[/tex] counterclockwise about the origin. The rotation rule for [tex]\(90^\circ\)[/tex] counterclockwise is [tex]\((x, y) \rightarrow (-y, x)\)[/tex]. We apply this to each of the vertices [tex]\(A'(1, -2)\)[/tex], [tex]\(B'(1, 1)\)[/tex], and [tex]\(C'(-3, -2)\)[/tex].
1. For vertex [tex]\(A'(1, -2)\)[/tex]:
[tex]\[ A'' = (-(-2), 1) = (2, 1) \][/tex]
2. For vertex [tex]\(B'(1, 1)\)[/tex]:
[tex]\[ B'' = (-(1), 1) = (-1, 1) \][/tex]
3. For vertex [tex]\(C'(-3, -2)\)[/tex]:
[tex]\[ C'' = (-(-2), -3) = (2, -3) \][/tex]
The vertices of the rotated [tex]\(\triangle A'' B'' C''\)[/tex] are:
[tex]\[ A'' = (2, 1), \quad B'' = (-1, 1), \quad C'' = (2, -3) \][/tex]
### Congruency Check
To determine if [tex]\(\triangle A B C\)[/tex] is congruent to [tex]\(\triangle A'' B'' C''\)[/tex], we compare the side lengths of both triangles.
1. Original triangle [tex]\(\triangle A B C\)[/tex]:
[tex]\[ \text{Side } AB = \|A - B\| = \sqrt{(-3 - (-3))^2 + (1 - 4)^2} = \sqrt{0^2 + (-3)^2} = 3 \][/tex]
[tex]\[ \text{Side } BC = \|B - C\| = \sqrt{(-3 - (-7))^2 + (4 - 1)^2} = \sqrt{4^2 + 3^2} = \sqrt{16 + 9} = 5 \][/tex]
[tex]\[ \text{Side } CA = \|C - A\| = \sqrt{(-7 - (-3))^2 + (1 - 1)^2} = \sqrt{(-4)^2 + 0^2} = 4 \][/tex]
2. Rotated triangle [tex]\(\triangle A'' B'' C''\)[/tex]:
[tex]\[ \text{Side } A''B'' = \|A'' - B''\| = \sqrt{(2 - (-1))^2 + (1 - 1)^2} = \sqrt{3^2 + 0^2} = 3 \][/tex]
[tex]\[ \text{Side } B''C'' = \|B'' - C''\| = \sqrt{(-1 - 2)^2 + (1 - (-3))^2} = \sqrt{(-3)^2 + 4^2} = \sqrt{9 + 16} = 5 \][/tex]
[tex]\[ \text{Side } C''A'' = \|C - A\| = \sqrt{(2 - 2)^2 + (-3 - 1)^2} = \sqrt{0^2 + (-4)^2} = 4 \][/tex]
Since the side lengths of [tex]\(\triangle A B C\)[/tex] and [tex]\(\triangle A'' B'' C''\)[/tex] match, the triangles are congruent.
### Conclusion:
Yes, [tex]\(\triangle ABC\)[/tex] is congruent to [tex]\(\triangle A'' B'' C''\)[/tex].
Thus, we have provided complete and detailed steps to answer each part of the problem correctly.
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.